TEACHING DIGITAL NATIVES: IDENTIFYING COMPETENCIES FOR MOBILE LEARNING FACILITATORS IN DISTANCE EDUCATION - Makoe, Mpine (South African Journal of Higher Education, 2016)
The use of mobile technologies in education has had a major impact on the pedagogy as known and understood by many academics in distance education institutions. Teaching using new technologies requires a variety of skills that are different from what most teachers are familiar with. Therefore, teachers need to be trained on how to use these new devices and how to integrate them into their own practice. The aim is to ensure that technology is not perceived as an add-on but as an integral part of the curriculum. The purpose of this paper therefore is to identify knowledge and skills that are needed to perform the role of a mobile learning facilitator with the aim of developing a professional development programme that is responsive to the competencies required.